Academic listening: What non-ESL lecturers should know / Tengku Intan Suzila Tengku Sharif and Mohd Yusri Mohamad Noor - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri (Universiti Teknologi MARA Cawangan Pahang, 2005)
This paper attempts to assist content-based/non-ESL lecturers (i.e. lecturers who teach Science & Technology subjects, etc. in English) of ESL environment, to make their lectures more exciting and productive for students' comprehension. Differences of first and second language academic listening processes will be put forward as a discussion to lead to an understanding of academic listening comprehension in an ESL environment for the knowledge of non-ESL lecturers. Functional pedagogical implication is set forth as a tool to guide non-ESL lecturers in their daily task.